Hungarian Monitoring, 8 January 1990 . [Magyar rádiófigyelő], 1990. január 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Chronicle of Romanian events, first Securitate trials - Fierce conflicts at GDR roundtable talks - Comecon summit - Christmas rehabilitated in the USSR - Lithuanian CP - More tension and shootings in Karabakh Domestic Affairs: - Gyula Horn in Israel - Dunagate affair: Military Supreme Prosecutor investigates, Constitutional Court's examination - HUF 700 million financial support from the budget for political parties - Képcsarnok picture gallery staff on strike Economy: - Hungarian government delegation in Bulgaria for Comecon 45th council meeting - Uranium mines in Pécs - Price increases Külpolitika: - Eseménykrónika Romániából, első Securitate perek - Merev szembenállás az NDK kerekasztal tárgyalásokon - KGST-csúcs - Rehabilitálták a SZU-ban a karácsonyt - A litván KP ügye - Ismét feszültség, lövöldözés Karabahban Belpolitika: - Horn Gyula Izraelben - Dunagate-ügy: nyomoz a Katonai Főügyészség, Alkotmánybíróság vizsgálata - 700 millió Ft-os támogatás a pártoknak a költségvetésből - Sztrájkoltak a Képcsarnok dolgozói Gazdaság: - Magyar kormányküldöttség Bulgáriába, a KGST 45. tanácsülésére - Pécsi Uránbánya - Áremelések